Determinants for sustainability of biodegradable plastics: a sequential exploratory mixed methods study - Taofeeq Durojaye, Moshood (2023)
Biodegradable materials can replace traditional plastics made from petroleum and help create more environmentally friendly products. They can be used in various applications, including packaging materials, garbage bags, catering items, food containers, laminating papers, golf tees, sanitary items, and agricultural applications. The key characteristic of biodegradable products is that they can break down into harmless substances over a specific period of time, completing their life cycle. However, for the widespread adoption of biodegradable plastics, it is essential to convince consumers, manufacturers, and regulators about their effectiveness. A study was conducted to investigate the factors influencing the sustainability of biodegradable plastics. The study followed a mixed-method approach, starting with qualitative research involving case studies with non-governmental organizations, government agencies, and biodegradable plastic producers. The qualitative research revealed that both organizational and individual factors play a significant role in determining the sustainability of biodegradable plastics. This led to the development of a conceptual research model. The model integrated several theories, such as the theory of planned behaviour, triple bottom line, the theory of green purchase behaviour, the norm activation theory, and the value-belief-norm theory. To gather data for the study, questionnaires were distributed online to plastic users in Malaysia who were 15 years old and above. A total of 316 responses were analyzed using PLS-SEM analysis. The results partially supported the research model. The study's findings have theoretical implications for biodegradable plastics research in developing markets. They also suggest that individual characteristics strongly influence the sustainability of biodegradable plastics and are important factors in determining behavioural intentions related to sustainability, such as purchasing environmentally friendly packaged food products. The study provides practical implications for government and corporate sectors to design effective strategies encouraging consumers to choose biodegradable plastics. Regular awareness campaigns should be conducted to increase consumer engagement in environmental concerns and reduce the use of non-eco-friendly packaging in the public sector. Policymakers can utilize social campaigns that focus on environmental self-identities to gradually shift sustainability behavioural intentions and promote the use of biodegradable plastics. Organizations can also incorporate environmental self-identity and participation in their marketing communications to raise awareness about biodegradable products and improve public perception.